PENGARUH PENERAPAN MODEL PEMBELAJARAN TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR - Elvi Syukri; Ilmiyati Rahmy Jasril (Universitas Negeri Padang, 2019)
The purpose of this study was to determine the effect of the application of the Cooperative Learning model of the Team Assisted Individualization (TAI) type to the learning outcomes of Basic Electricity and Electronics in class X TAV students at SMKN 1 Kinali. This type of research is a quasi experiment with a randomized control group only design. The sampling technique uses Simple Random Sampling. The research sample XTAV1 (control class) is applied to the conventional learning model and XTAV2 (experimental class) is applied to the TAI learning model. The research data are the posttest value of the experimental and control class. Then the normality test, homogeneity test and hypothesis test were analyzed. Based on the research data, the mean value of the control class was 76,30 and the experiment was 84,10. Hypothesis test results at a significant level α = 0,05 obtained tcount 3,14 and ttable 1,69 (tcount>ttable) can be identified Ho is rejected and Ha is accepted. The test results provide an interpretation of the significant influence of learning outcomes by applying the TAI learning model in the subjects of Basic Electricity and Electronics class X TAV in SMK N 1 Kinali. Keywords:TAI Learning Model, quasi experiment, Learning Outcomes